2022
DOI: 10.3389/fonc.2022.900712
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumor Fluorine‐18 Fluorodeoxydglucose (18F‐FDG) Is Associated With Cancer-Associated Weight Loss in Non-Small Cell Lung Cancer (NSCLC) and Portends Worse Survival

Abstract: AimTo investigate the diagnostic potential of and associations between tumor 18F‐FDG uptake on PET imaging and cancer-associated weight loss.Methods774 non-small cell lung cancer (NSCLC) patients with pre-treatment PET evaluated between 2006 and 2014 were identified. Using the international validated definition of cachexia, the presence of clinically significant pretreatment cancer-associated weight loss (WL) was retrospectively determined. Maximum Standardized Uptake Value (SUVMax) of 18F‐FDG was recorded and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…In cancer patients, the role of the Warburg effect in the pathogenesis of cancer cachexia is not studied as thoroughly, as in the nude mice. For instance, the Warburg effect was seen as responsible for weight loss in cancer patients 34–36 . In other studies, increased glucose turnover and hepatic gluconeogenesis were seen in cancer patients 12–14 …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In cancer patients, the role of the Warburg effect in the pathogenesis of cancer cachexia is not studied as thoroughly, as in the nude mice. For instance, the Warburg effect was seen as responsible for weight loss in cancer patients 34–36 . In other studies, increased glucose turnover and hepatic gluconeogenesis were seen in cancer patients 12–14 …”
Section: Discussionmentioning
confidence: 86%
“…For instance, the Warburg effect was seen as responsible for weight loss in cancer patients. [34][35][36] In other studies, increased glucose turnover and hepatic gluconeogenesis were seen in cancer patients. [12][13][14] Only patients with early pancreatobiliary cancer are eligible for curative surgery, and such patients may not have cachectic states.…”
Section: Discussionmentioning
confidence: 93%
“…Through the development of a retrospective clinical data set of 3,180 patients with gastrointestinal and pulmonary cancer, we have previously evaluated associations between the incidence of cachexia with pretreatment patient medication use, laboratory values, and positron emission tomography imaging in a search for potential diagnostic and interventional tools against this syndrome. [5][6][7] In these projects, we have consistently detected a significant influence of patient demographic characteristics on cachectic weight loss at the time of cancer diagnosis. Consequently, this study intends to further characterize the relationship between cachexia and patient race, ethnicity, and socioeconomic factors.…”
Section: Introductionmentioning
confidence: 90%
“…A recent review described how imaging modalities for quantitative and qualitative change in adipose tissue, organs, and muscle compartments are assessed for the diagnosis and monitoring of cancer cachexia [3]. Olaechea et al [4] reported a signi cant positive relationship between cancer-associated weight loss at diagnosis and increased primary tumor SUV max for 18 F-FDG uptake in patients with non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study has shown that 18 F-FDG uptake is higher in cachexia-inducing tumor cells than in non-cachexia tumor cells [5]. Potentially, escalated tumor glucose consumption, such as high 18 F-FDG uptake, is associated with the presence of a tumor phenotype that induces weight loss [4]. Previous studies have reported that body weight is closely related to physiological 18 F-FDG uptake by the liver [6,7].…”
Section: Introductionmentioning
confidence: 99%